2016
DOI: 10.1111/afe.12170
|View full text |Cite
|
Sign up to set email alerts
|

Weed seed granivory by carabid beetles and crickets for biological control of weeds in commercial lowbush blueberry fields

Abstract: 1 Weeds are one of the most limiting factors in the commercial production of lowbush blueberries Vaccinium angustifolium (Ericaceae). Sheep sorrel (Rumex acetosella) and hairy fescue (Festuca tenuifolia) are prominent weeds in lowbush blueberry fields. 2 Because the granivorous insects Harpalus rufipes (Carabidae) and Gryllus pennsylvanicus (Gryllidae) are common in lowbush blueberry fields when sheep sorrel and hairy fescue are dispersing seeds, we examined how granivorous insects can contribute to the biocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
7
2
Order By: Relevance
“…Among the populations of the three carabid species, P. rufipes showed an especially high frequency of detection for seeds. This finding is in accordance with the prior trophic characterization of this carabid species as a seed predator (Thiele 1977 ; Holland 2002 ) and laboratory feeding experiments that indicate that seeds are their preferred food source (Toft 2002 ; Cutler et al 2016 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the populations of the three carabid species, P. rufipes showed an especially high frequency of detection for seeds. This finding is in accordance with the prior trophic characterization of this carabid species as a seed predator (Thiele 1977 ; Holland 2002 ) and laboratory feeding experiments that indicate that seeds are their preferred food source (Toft 2002 ; Cutler et al 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…Detection frequencies of plant DNA were high—across all regions independently of carabid species, sex and sampling time. We hypothesize that the plant DNA detected in regurgitates mainly originates from consumed seeds as has been demonstrated in numerous studies (Tooley and Brust 2002 ; Honek et al 2003 ; Lundgren et al 2013 ; Daedlow et al 2014 ; Kulkarni et al 2015 ; Cutler et al 2016 ; Talarico et al 2016 ; Birthisel et al 2017 ). Our logic for this hypothesis is that while carabid beetles can eat fruit, pollen and sometimes plant leaves (Toft 2002 ), previous studies have shown that herbivory (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Beetles were brought to the laboratory in clear 1-liter plastic containers, and then transferred to sealable plastic cups (120 ml) containing a 50:50 v:v moistened peat and play sand mixture. Beetles were fed cat food (Whiskas; Mars Canada, Canada) until they were needed for the experiments (Cutler et al 2016). All beetles were collected within 2 wk of the start of an experiment and starved 60 h prior to the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore examined whether P. lucublandus and P. mutus consume seeds of two economically important weeds commonly found in lowbush blueberry fields. Feeding of these species was compared with that of Harpalus rufipes (De Geer), a carabid known to feed on seeds (Harrison and Gallandt 2012, Cutler et al 2016).…”
mentioning
confidence: 99%
“…Most of the seeds were located on the soil surface, similar to that reported for weed seeds in other no‐till systems (Yenish et al ., ; Cardina et al ., ), which provides opportunities for seedbank management. Certain species of predatory ground beetles consume F. filiformis seeds in lowbush blueberry fields (Cutler et al ., ), and management practices that support the presence of these insects may therefore contribute to significant F. filiformis seed losses to predation. Festuca filiformis seeds are also susceptible to heat (White & Boyd, ), and although burn pruning does not consistently reduce F. filiformis density (Penney et al ., ), the location of most seeds on the soil surface suggests that burn pruning may be an effective method of seedbank management for these grasses.…”
Section: Discussionmentioning
confidence: 99%